Six ways to get a grip on co-creating curriculum with patients - Graves, L; Soleas, E; Turnnidge, J; Cofie, N; Jackson, M; Mulder, J; Karazivan, P; Descôteaux, A; Balounaïck-Arowas, V; Van Hoorn, R; Dalgarno, N (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
There is growing recognition of the value and importance of patient engagement in medical education. In this work, we reflect on both the literature on patient engagement and our experiences with a recent initiative focused on the co-creation of educational curricula with patient and healthcare professional partners and offer recommendations for educators and researchers interested in engaging in patient partnerships to develop medical education curriculum. We adopted a co-creation approach, in which patient and healthcare professional Subject Matter Experts (SMEs) were provided an opportunity to co-create curricular material. During the curricular development period, we experienced successes and challenges that allowed us to develop six recommendations to “get a grip” on adopting co-creation approaches to curriculum development in medical education. By applying these recommendations, medical educators can help foster meaningful and sustainable patient partnerships.